2017
DOI: 10.1111/mmi.13853
|View full text |Cite
|
Sign up to set email alerts
|

Don’t let sleeping dogmas lie: new views of peptidoglycan synthesis and its regulation

Abstract: SUMMARY Bacterial cell wall synthesis is the target for some of our most powerful antibiotics and has thus been the subject of intense research focus for more than 50 years. Surprisingly, we still lack a fundamental understanding of how bacteria build, maintain and expand their cell wall. Due to technical limitations, directly testing hypotheses about the coordination and biochemistry of cell wall synthesis enzymes or architecture has been challenging, and interpretation of data has therefore often relied on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
108
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 122 publications
0
108
0
Order By: Relevance
“…The cell wall is a crucial structural feature for the vast majority of bacteria and is mainly composed of a rigid, yet elastic, covalently‐bound network of peptidoglycan (PG) strands. PG has an oligomeric glycan backbone that is assembled by glycosyltransferases (GTs, RodA/FtsW and class A Penicillin Binding Proteins [aPBPs]) (Cho et al , ; Leclercq et al , ; Zhao et al , ; Taguchi et al , ) through the polymerization of N ‐acetylglucosamine (NAG)‐ N ‐acetylmuramic acid (NAM) heterodimers. These PG strands are crosslinked to adjacent strands primarily by the transpeptidase domains of aPBPs and bPBPs via short peptides attached to the NAM residues, resulting in the strong, mesh‐like sacculus.…”
Section: Introductionmentioning
confidence: 99%
“…The cell wall is a crucial structural feature for the vast majority of bacteria and is mainly composed of a rigid, yet elastic, covalently‐bound network of peptidoglycan (PG) strands. PG has an oligomeric glycan backbone that is assembled by glycosyltransferases (GTs, RodA/FtsW and class A Penicillin Binding Proteins [aPBPs]) (Cho et al , ; Leclercq et al , ; Zhao et al , ; Taguchi et al , ) through the polymerization of N ‐acetylglucosamine (NAG)‐ N ‐acetylmuramic acid (NAM) heterodimers. These PG strands are crosslinked to adjacent strands primarily by the transpeptidase domains of aPBPs and bPBPs via short peptides attached to the NAM residues, resulting in the strong, mesh‐like sacculus.…”
Section: Introductionmentioning
confidence: 99%
“…The rotation of MreB in the cytoplasm is coupled with synthesis of PG occurred in the periplasm through a transmembrane protein RodZ (Domínguez‐Escobar et al, ; Garner et al, ; Morgenstein, Nguyen, & Gitai, ; van Teeffelen et al, ). MreB forms Rod complex with PG‐synthesizing enzymes, such as penicillin‐binding proteins (PBPs) (Blaauwen et al, ; Zhao, Patel, Helmann, & Dörr, ). Because MreB is a scaffold protein for the Rod complex, deletion of mreB gene or treatment of wild‐type (WT) cells with A22, which inhibits assembly of MreB, results in change of cell shape from rod to round (Bean et al, ; Doi et al, ; Iwai, Nagai, & Wachi, ; van den Ent et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, aPBP activity was increased ( Lai et al, 2017 ) upon over-expression of the DD-endopeptidase MepS, which cleaves peptide bonds ( Singh et al, 2012 ). Therefore, Rod complex and aPBPs might serve different functions despite catalyzing the same chemical reactions ( Zhao et al, 2017 ; Pazos et al, 2017 ). In agreement with this viewpoint, recent work in the gram-positive Bacillus subtilis showed that the two machineries have opposing actions on cell diameter and lead to either circumferentially organized or disordered cell-wall deposition ( Dion et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%